Republic of Poland : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that the fiscal deficit of the Republic of Poland widened sharply in 2001, reflecting both automatic stabilizers and a 1\2 percent increase in the structural deficit. State (central government) primary expenditures (excluding one-off transfers) rose relative to GDP by 1 percentage point, notwithstanding cutbacks late in the year. Two factors accounted for this rise: significant increases in transfers and subsidies to households, agricultural and state enterprises, as well as wages; and outcomes for inflation and growth that were far below budget projections.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet